External validation of models to predict the outcome of pregnancies of unknown location: a multicentre cohort study. (7th October 2020) - Christodoulou, E; Bobdiwala, S; Kyriacou, C; Farren, J; Mitchell‐Jones, N; Ayim, F; Chohan, B; Abughazza, O; Guruwadahyarhalli, B; Al‐Memar, M; Guha, S; Vathanan, V; et al.
Abstract : Objective: To validate externally five approaches to predict ectopic pregnancy (EP) in pregnancies of unknown location (PUL): the M6P and M6NP risk models, the two‐step triage strategy (2ST, which incorporates M6P), the M4 risk model, and beta human chorionic gonadotropin ratio cut‐offs (BhCG‐RC). Design: Secondary analysis of a prospective cohort study. Setting: Eight UK early pregnancy assessment units. Population: Women presenting with a PUL and BhCG >25 IU/l. Methods: Women were managed using the 2ST protocol: PUL were classified as low risk of EP if presenting progesterone ≤2 nmol/l; the remaining cases returned 2 days later for triage based on M6P. EP risk ≥5% was used to classify PUL as high risk. Missing values were imputed, and predictions for the five approaches were calculated post hoc. We meta‐analysed centre‐specific results. Main outcome measures: Discrimination, calibration and clinical utility (decision curve analysis) for predicting EP. Results: Of 2899 eligible women, the primary analysis excluded 297 (10%) women who were lost to follow up. The area under the ROC curve for EP was 0.89 (95% CI 0.86–0.91) for M6P, 0.88 (0.86–0.90) for 2ST, 0.86 (0.83–0.88) for M6NP and 0.82 (0.78–0.85) for M4. Sensitivities for EP were 96% (M6P), 94% (2ST), 92% (N6NP), 80% (M4) and 58% (BhCG‐RC); false‐positive rates were 35%, 33%, 39%, 24% and 13%. M6P and 2ST had the best clinical utility and good overall calibration, with modest variability between centres. Conclusions: 2ST and M6P performed best for prediction and triage in PUL. Tweetable abstract: The M6 model, as part of a two‐step triage strategy, is the best approach to characterise and triage PULs. Tweetable abstract: The M6 model, as part of a two‐step triage strategy, is the best approach to characterise and triage PULs.